PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN DISCOVERY LEARNING DI KELAS XI IPS2 SMA NEGERI 3 SAMARINDA - Suriaty (De Fermat : Jurnal Pendidikan Matematika, 2021)
This classroom action research aims to improve the mathematics learning outcomes of class XI IPS2 students at SMA Negeri 3 Samarinda through Discovery Learning on mathematical induction materials, linear and matrix programs, and was carried out in August – September 2019 with 36 students as research subjects and research objects. is learning Discovery Learning. The instruments used are assignments, end-of-cycle tests and observations. Assignments consist of group and individual assignments. The test is carried out at the end of each cycle. Observations were carried out at each meeting and during the learning process. The test questions in each cycle are in the form of descriptions. Data analysis using descriptive statistics. The implementer of the lesson is a mathematics teacher at SMA Negeri 3 Samarinda, the observer is a researcher. The results of data analysis showed an increase in the average value at the end of each cycle. The final value of the cycle is obtained from the value of group and individual assignments, as well as the test scores of each cycle. In the first cycle the basic value was 51.1 and the final value was 55.5 with an increase of 4.4. In the second cycle the basic value is 55.5 and the final value is 68.3 with an increase of 12.8. In the third cycle, the basic score was 68.3 and the final grade was 78.3 with an increase of 10. The conclusion was that through Discovery Learning, the mathematics learning outcomes of XI2 grade students of SMA Negeri 3 Samarinda increased.